The Impact of AI-Based Learning Applications on Students Self-Regulated Learning Using the Personalized Learning Method - Syarifah Suryana; Israwati Hamsar (Jurusan Teknik Informatika dan Komputer, 2025)
This study examines the impact of AI-based learning applications on students' self-regulated learning using the Personalized Learning method. The research employs an experimental design with two groups: the experimental group using AI-based applications and the control group following traditional learning methods. Data were collected through questionnaires, interviews, and learning outcome tests. The results show that AI-based applications significantly enhance students' self-regulated learning and academic performance compared to traditional learning. The use of this application has proven effective in supporting self-regulated learning and improving students' academic outcomes.